SOURCES OF FINANCING SMALL BUSINESS INVESTMENT ACTIVITIES AND THEIR COMPOSITION (International Congress on Economics, Management and Business Studies, 2026)
Small business investment activities represent one of the most important drivers of economic development in both developed and developing countries. They contribute significantly to GDP growth, employment creation, innovation diffusion, regional development, and poverty reduction. In modern economic systems, small businesses are considered the backbone of private sector development, as they ensure flexibility, adaptability, and competitiveness in rapidly changing market conditions. However, the sustainability and expansion of small business investment activities largely depend on the availability, accessibility, and structure of financing sources.